1995
DOI: 10.1073/pnas.92.22.10152
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of putative antigens encoded by pigment genes in mouse melanomas at different stages of malignant progression.

Abstract: Cutaneous melanomas of Tyr-SV40E transgenic mice (mice whose transgene consists of the tyrosinase promotor fused to the coding regions of simian virus 40 early genes) strikingly resemble human melanomas in their development and progression. Unlike human melanomas, the mouse tumors all arise in genetically identical individuals, thereby better enabling expression of specific genes to be characterized in relation to advancing malignancy. The products of pigment genes are of particular interest because peptides d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…These include various tissues of the central nervous system such as substantia nigra, forebrain and midbrain, as well as melanocytes and melanoma cells (Orlow et al, 1995;Bernd et al, 1994;Tief et al, 1998). Since cancer cells can often ectopically express genes that are characteristic of other cell lineages, we examined a panel of non-melanoma human cancer cell lines for the expression of TYRP2.…”
Section: Tyrp2 Is Not Expressed In a Panel Of Non-melanoma Human Cancmentioning
confidence: 99%
“…These include various tissues of the central nervous system such as substantia nigra, forebrain and midbrain, as well as melanocytes and melanoma cells (Orlow et al, 1995;Bernd et al, 1994;Tief et al, 1998). Since cancer cells can often ectopically express genes that are characteristic of other cell lineages, we examined a panel of non-melanoma human cancer cell lines for the expression of TYRP2.…”
Section: Tyrp2 Is Not Expressed In a Panel Of Non-melanoma Human Cancmentioning
confidence: 99%
“…10,11 Several enzymes that participate in melanogenesis, including tyrosinase, tyrosinase-related protein-1 (TRP-1), tyrosinase-related protein-2 (TRP-2), and Pmel17/Silver, are expressed in pigmented melanomas. 7,8,13 Although many of these melanogenic enzymes are absent from amelanotic melanomas, TRP-2 (DOPAchrome tautomerase) appears to be retained in many unpigmented melanomas. 7,8 In fact, recent studies have suggested that TRP-2 may be a good candidate for immunotherapy of amelanotic melanoma.…”
mentioning
confidence: 99%
“…7,8,13 Although many of these melanogenic enzymes are absent from amelanotic melanomas, TRP-2 (DOPAchrome tautomerase) appears to be retained in many unpigmented melanomas. 7,8 In fact, recent studies have suggested that TRP-2 may be a good candidate for immunotherapy of amelanotic melanoma. 7,8 In the mouse, TRP-2 is encoded by the slaty locus.…”
mentioning
confidence: 99%
See 2 more Smart Citations